2000
DOI: 10.1046/j.1365-2206.2000.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the care: the qualities sought of social workers by foster carers

Abstract: Given that foster carers are a scarce resource it is essential that every effort is made to retain their services. This paper considers the role played by social workers in this endeavour. The results reported here form part of larger study, involving seven local authorities, concerned with the wider issues of supporting foster placements. The paper describes the qualities sought of social workers by foster carers and discusses the relationship between these qualities and the likelihood that carers will contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 12 publications
2
51
0
Order By: Relevance
“…One significant contributor to foster parent attrition was placement breakdown (Fisher et al 2000;Leschied et al 2004).…”
mentioning
confidence: 98%
“…One significant contributor to foster parent attrition was placement breakdown (Fisher et al 2000;Leschied et al 2004).…”
mentioning
confidence: 98%
“…Such unfortunate endings also have negative effects on the foster care program itself (Patten, 2005;Smith, 1994) because they can lead to demoralization of the foster parents and even make them want to stop collaborating with the placement program (Brown & Calder, 1999;Fisher, Gibbs, Sinclair, & Wilson, 2000;Gilbertson & Barber, 2003;Vanderfaeillie, Van Holen, & Coussens, 2008). Nor should the discouraging effects that such failures can have on child welfare workers be neglected (Aldgate & Hawley, 1986;Berridge & Cleaver, 1987;Cautley, 1980;Wade et al, 1998).…”
Section: Rates Of Breakdown and Its Consequencesmentioning
confidence: 99%
“…A review of the available literature indicated that challenges facing foster parents with a child who has a diagnosis associated with prenatal substance exposure include childrenÕs conduct problems (Brooks & Barth, 1998), as well as obtaining specialized educational (Guinta & Streissguth, 1988), financial (Rhodes, Orme, & Buehler, 2001), and emotional support (Fisher, Gibbs, Sinclair, & Wilson, 2000). However, few of these studies have focused on the challenges as defined by foster parents themselves.…”
Section: Problem Statementmentioning
confidence: 98%
“…In addition to the availability and accessibility of material support, such as worker contact (Hess, 1998) financial compensation (Rhodes, Orme & Buehler, 2001), and respite (Hay, 1999), the impact of personal recognition and appreciation for foster parents has been recognized as influential on placement outcome (Fisher et al, 2000). Perceived lack of support and empathy from professionals has been identified as a significant factor in placement breakdown (Hess, 1998), and, conversely, feelings of control and connectedness increase foster parent efficacy and placement satisfaction (Jones, 1999;Weiner, 1994).…”
Section: Concept Six: Taken For Grantedmentioning
confidence: 99%